2015
DOI: 10.1682/jrrd.2014.09.0210
|View full text |Cite
|
Sign up to set email alerts
|

Physical performance and self-report outcomes associated with use of passive, adaptive, and active prosthetic knees in persons with unilateral, transfemoral amputation: Randomized crossover trial

Abstract: Abstract-Prosthetic knees are a vital component in an artificial limb. Contemporary knees include passive (mechanical), adaptive (computerized), or active (motorized) control systems and have the potential to mitigate amputation-related functional impairments and activity limitations. A 14 mo randomized crossover trial was conducted. Participants (n = 12, mean age = 58 yr) were tested under three conditions: passive control (existing knee), adaptive control (Ossur Rheo Knee II), and active control (Ossur Power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 94 publications
(153 reference statements)
2
76
1
1
Order By: Relevance
“…There is also ambiguity when looking at the time needed to descent a slope. Both a decrease 27,36 as an increase in time 34 have been reported while using a MPK compared to the use of a NMPK.…”
Section: Environmental Obstacle Negotiationmentioning
confidence: 98%
See 4 more Smart Citations
“…There is also ambiguity when looking at the time needed to descent a slope. Both a decrease 27,36 as an increase in time 34 have been reported while using a MPK compared to the use of a NMPK.…”
Section: Environmental Obstacle Negotiationmentioning
confidence: 98%
“…Hafner et al 34 found no differences in walking speed, whereas Meier et al 35 found an increase in walking speed while using a MPK to navigate an obstacle course.…”
Section: Environmental Obstacle Negotiationmentioning
confidence: 99%
See 3 more Smart Citations